Dampak Transformational Safety Leadership dan Safety Culture terhadap Safety Behavior Melalui Safety Motivation Awak Kapal pada PT. Pelayaran Karana Line Cabang Pulau Batam - Ramadhan, Firhand Aulia; Setyawati, Aswanti; Pahala, Yosi; Pahrudin, Cecep; Thamrin, Muhammad (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the impact of transformational leadership and culture on safety behavior through the motivation of crew members at PT. Pelayaran Karana Line branch in Pulau Batam. Using a quantitative research method, data were collected through questionnaires distributed to the crew members. The results of the study indicate that transformational leadership and organizational culture have a positive and significant impact on safety behavior, mediated by the motivation of the crew. These findings provide practical implications for the company's management in enhancing workplace safety onboard ships.